Natural convection melting of NEPCM in a cavity with an obstacle using lattice Boltzmann method. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The aim of this study is to apply an enthalpy‐based lattice Boltzmann method with multi distribution function model, to investigate melting process with natural convection inside a cavity with an obstacle. The cavity is filled with water (ice)‐based nanofluid containing copper nanoparticles.Design/methodology/approach – This methodology eliminates the requirement of satisfying conditions at the phase change front. The combination of lattice D2Q9 and D2Q5 models is implemented to determine the density, velocity and temperature fields. The simulations are carried out for Rayleigh number of 105, various volume fractions of the nanoparticles and various positions of the cubic obstacle.Findings – The predicated results demonstrate that the use of nanoparticles leads to enhancement of thermal conductivity of nano‐enhanced phase change materials in comparison with conventional PCMs. When the position of the obstacle changes from the top to the bottom of the cavity the melting rate increases 75 percent. The numerical study indicates that by increasing the solid concentration from 0 to 0.04, the heat release enhances 52.7, 41.2 and 30 percent when the obstacle is located on the top, middle and bottom sections of the cavity, respectively. It is also observed that, the employment of nanoparticles is more effective when the heat conduction dominates.Originality/value – The main unacceptable property of most PCMs is their low thermal conductivity, and hence, heat transfer enhancement using nanofluid will be useful for thermal energy storage applications.